2015
DOI: 10.1007/s10956-015-9572-6
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of Hands-on STEM Engagement Activities with Positive STEM Dispositions in Secondary School Students

Abstract: This study examines positive dispositions reported by middle school and high school students participating in programs that feature STEM-related activities. Middle school students participating in school-to-home hands-on energy monitoring activities are compared to middle school and high school students in a different project taking part in activities such as an after-school robotics program. Both groups are compared and contrasted with a third group of high school students admitted at the eleventh grade to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 27 publications
3
73
0
4
Order By: Relevance
“…Osaamisen kehittyminen ja teknologiasta kiinnostumisen tulkittiin olevan yhteydessä aktiiviseen hands-on -tyyppiseen oppimiseen, joka on yhteydessä ja koskee ympäröivää reaalimaailmaa. (Christensen, Knezek & Tyler-Wood, 2015.) Kansainvälisessä robotiikkakilpailussa toteutetun tutkimuksen mukaan (N=796, 26 maata, 80 % osallistujista poikia) osallistuminen kilpailuun robotteja rakentamalla ja ohjelmoimalla lisäsi oppilaiden mukaan ohjelmointi-, ryhmätyö-ja kommunikointitaitoja sekä kiinnostusta matemaattis-luonnontieteellisiin aloihin ja teknologiaan (Eguchi, 2016).…”
Section: Teknologian Oppiminen Toiminnallisestiunclassified
See 1 more Smart Citation
“…Osaamisen kehittyminen ja teknologiasta kiinnostumisen tulkittiin olevan yhteydessä aktiiviseen hands-on -tyyppiseen oppimiseen, joka on yhteydessä ja koskee ympäröivää reaalimaailmaa. (Christensen, Knezek & Tyler-Wood, 2015.) Kansainvälisessä robotiikkakilpailussa toteutetun tutkimuksen mukaan (N=796, 26 maata, 80 % osallistujista poikia) osallistuminen kilpailuun robotteja rakentamalla ja ohjelmoimalla lisäsi oppilaiden mukaan ohjelmointi-, ryhmätyö-ja kommunikointitaitoja sekä kiinnostusta matemaattis-luonnontieteellisiin aloihin ja teknologiaan (Eguchi, 2016).…”
Section: Teknologian Oppiminen Toiminnallisestiunclassified
“…Tulosten perusteella tulevat opettajat tunnistavat hyvin teknologiakasvatuksen toteuttamisen ja kehittämisen kannalta keskeisiä jo aiemmassa tutkimuksessa esille tulleita elementtejä: opetuksen ja oppimisen ilmiölähtöisyys (Hill, 1998;Hill & Smith, 1998;Parkinson & Hope, 2009;Twyford & Järvinen, 2000) ja toiminnallisuus (Christensen, 2015;Eguchi, 2016;Naizer ym., 2014). Nämä molemmat yhdessä toimivat elementteinä mielekkäille oppimiskokemuksille.…”
Section: Johtopäätöksetunclassified
“…They detected a strong, positive relationship between a teacher's gender and her/his students' performance and attitudes, with female teachers having more impact in this regard than their male counterparts. Christensen, Knezek and Tyler-Wood (2015) quote from a study (initially reported on by Sadler, Sonnert, Hazari & Tai, 2012) involving 6,000 American high school students, which found that the odds of male students pursuing a Science, Technology, Engineering or Mathematics (STEM) career are almost three times higher than for females. Almost 40% of the pre-service mathematics teachers, who participated in this inquiry are female, which is a positive notion.…”
Section: Testing For Significant Differences Between Subgroups Of Parmentioning
confidence: 99%
“…A change in current classroom practices is needed if schools are going to attract more students to STEM fields. More hands-on, real-life problem solving can help generate excitement among students and has the potential to attract more students to STEM (Christensen, Knezek, & Tyler-Wood, 2015). One way to provide more meaningful problem solving activities is problem-based learning in science, technology, engineering, and mathematics.…”
Section: Improving High School Math Teachers' Confidence and Skills Imentioning
confidence: 99%
“…Active, hands-on learning helps engage students in activities that relate to the real world. Christensen, Knezek, and Tyler-Wood (2015) found involving students in active learning "may be effective in promoting (or retaining) positive interest in STEM content and careers. "…”
Section: Improving High School Math Teachers' Confidence and Skills Imentioning
confidence: 99%